Reciclaje de la basura marina en el malecón de la parroquia rural de Puerto Bolívar. - Castro Jaén, Alejandro Junior (2015)
As is the coastal profile of the rural parish of Puerto Bolívar a lot of garbage extends in its more variable classification from plastic, cardboard, chemicals, dead animals, among others, which are mostly waste from human activities deliberately or accidentally float on lakes, seas, oceans and rivers. Oceanic debris tends to accumulate in corners of the shores of the Sea (large rotating currents), and the coastline is washed to run aground and is also known as beach litter. The route of garbage starts in the streets and the rain comes in the sewers of the city and later lead to some river, the river transports waste at sea is estimated that 20% of waste is originated in the sea and 80% are produced on land, behold the reason for the scientific paper recycling.